Междисциплинарные проекты как способ формирования компетенций при реализации образовательных программ - Irina G. Ignatova; Alexander G. Balashov; Natella Yu. Sokolova (Высшее образование в России)
Interdisciplinary project is one of the effective educational technologies used in MIET as a part of the competence building approach. The experience in the development of the methodical documents for such projects implementation is described in this paper. The list of recommended structural methodological elements for interdisciplinary project realization as a students’ competence building tool is proposed. In addition to this, the content of methodological support preparation stages is provided. The description of the courses sequence in the interdisciplinary project is given as an example.